Informes histórico-jurídicos sobre la protección constitucional del derecho a vivir - Juan I. Larrea Holguín (Ius Humani. Jornal do direito, 2008)
Here are collected two reports about the possibility of decriminalizing abortion in Ecuador. Although they were issued on the basis of two bills that failed in the legislature, historical and legal arguments discharges there, take advantage for further development doctrinal matter.